Garderobut . The Wardrobe - Dyulgerov, Georgi (Bulgaria, 1974)
Duration: 01:06:00 Absurd grotesque. A young couple dreams of having a wardrobe, which would make their small attic a cozier place to live in. When they buy it, the wardrobe with its built-in television set begins to totally manipulate their life - it controls their actions, interferes in their intimacy and finally sets strict rules of conduct. Its ambition is to make high-educated and well-behaving people in a world dominated by order. The young woman, inclined to a compromise with the dictatorship, is more compliant with the orders but falls into total subjection after spending some time in the wardrobe. The man who tries to fight the machine with a hammer and a screw-driver, is finally convinced into conformity. At the end the young man is woken from his night-dreaming by his wife who is just bringing home their new wardrobe.